STUDY OF SENSITISATION TO MOULD FUNGI IN PATIENTS WITH MICROBIAL ECZEMA - Popova, I.B.; Kaydashev, I.P.; Yemchenko, Ya.O.; Vasylyeva, K.V.; Bezeha, O.V. (World of Medicine and Biology, 2024)
There is no single concept of the etiology of eczema, and the complex links in of the pathogenesis of eczema, the formation of which reflects the dynamic and interrelated changes in the functions of various organs and systems of the body. One of the most important pathogenetic mechanisms of eczema, as well as allergy in general, is the development of immune reactions caused by exogenous allergens. Unlike pollen allergens, mold allergens are more complex in structure and cause not only IgE-mediated allergy, as each of their components (spores, mycelium, hyphae) to a certain extent has allergenic potential and can cause a multidirectional immune response. 78 (90.7 %) patients had an increased level of specific IgE to at least one of the investigated mold allergens. The highest concentration level of IgE (more than 17.5) was observed for the allergen of the fungus Penicillium notatum in 15.1 % of patients with chronic microbial eczema. The results of the study can be the basis for further study of mycogenic sensitisation.